2004
DOI: 10.1210/en.2003-1615
|View full text |Cite
|
Sign up to set email alerts
|

Orchidectomy, But Not Ovariectomy, Regulates Angiotensin II-Induced Vascular Diseases in Apolipoprotein E-Deficient Mice

Abstract: In humans, the incidence and severity of abdominal aortic aneurysms (AAA) are greater in males than in females. Chronic infusion of angiotensin II (AngII) into apolipoprotein E-deficient (apoE(-/-)) mice promotes atherosclerosis and causes the formation of AAAs. Just as human males are more susceptible to developing AAAs, male mice are more susceptible to AngII-induced AAAs. We hypothesized that sex steroid hormones mediate gender differences in AngII-induced AAA through regulation of the renin-angiotensin sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
129
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(154 citation statements)
references
References 49 publications
12
129
2
Order By: Relevance
“…67 Androgens increased the incidence of AngII-induced AAA in mice and had the ability to stimulate MMP2 expression. 75 The effects of androgens on AAA formation include stimulation of components of the renineangiotensin system producing either increased synthesis or responsiveness to AngII. 75 Despite the many detrimental effects of testosterone, some studies revealed that androgens exert atheroprotective effects against cardiovascular disease at least in the elderly people, mediated by the androgen receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…67 Androgens increased the incidence of AngII-induced AAA in mice and had the ability to stimulate MMP2 expression. 75 The effects of androgens on AAA formation include stimulation of components of the renineangiotensin system producing either increased synthesis or responsiveness to AngII. 75 Despite the many detrimental effects of testosterone, some studies revealed that androgens exert atheroprotective effects against cardiovascular disease at least in the elderly people, mediated by the androgen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AAA was strikingly reduced in orchiectomized male mice compared with sham controls (18% vs. 85%) and was similar to the incidence observed in female mice (25%). 75 Castrated male mice and rats treated with dihydrotestosterone and testosterone, respectively, showed a significant increase in the incidence of AAA compared with only castrated males. 69,76 Recently, a study by the same group showed that castration reduced the progressive lumen dilatation of established AAAs, suggesting that androgens also play a role in the progression of AAAs in male mice and that TGFb and Serpine1 may be targets of testosterone action in the progression of AAA.…”
Section: The Effect Of Castration On Aaa Parametersmentioning
confidence: 94%
See 1 more Smart Citation
“…5 Thus, AngII provides a common stimulus for atherosclerosis and AAAs, but the development of these pathologies appears to occur via distinct mechanisms. 6 The specific receptor regulating the formation of AngII-induced atherosclerosis has not been determined. A role for AT1 receptors in AngII-induced AAAs has been demonstrated by inhibition with losartan, although the contribution of AT1a versus AT1b receptors has not been defined.…”
mentioning
confidence: 99%
“…1 Currently, the reasons for the male propensity for AAA are not known, but maybe linked to sex hormones, as in experimental models androgens have been positively linked to aortic dilatation. 2 The production, metabolism and response to sex hormones are controlled by an array of enzymes and receptors, including steroid 5a reductase, aromatase (estrogen synthetase), androgen and estrogen receptors. 3,4 Steroid 5a reductase enzymes are responsible for the conversion of testosterone to the more potent androgen dihydrotestosterone.…”
Section: Introductionmentioning
confidence: 99%